Po obu stronach muru berlińskiego. Poetyka przekładu wybranych opowiadań Iwaszkiewicza w języku niemieckim - Fimiak-Chwiłkowska, Anna (Załącznik Kulturoznawczy, 2024)
The consideration of this article focuses on the short stories of Jarosław Iwaszkiewicz published in the GDR and FRG in the period from 1946–1989. Its purpose, after pointing out the translations of Iwaszkiewicz’s works into German in both publishing markets, is to emphasize the role of the category of the poetics of translation. The analysis, preceded by a discussion of the author’s reception on both sides of the Berlin Wall, focuses on successive translations of the same text within the translation series. Silhouettes of individual translators are also included, as well as special contexts that may have influenced the final shape of the translation. Excerpts from the short stories Panny z Wilka, Brzezina and Matka Joanna od Aniołów will be used to illustrate the category of translation poetics.